Pertanggungjawaban Pidana terhadap Pelaku Memperdagangkan Satwa yang Dilindungi dalam Perspektif Peraturan Perundang-Undangan di Indonesia - Hutauruk, Jasa Alex Parlinggoman; Hafrida, Hafrida; Liyus, Herry (Wajah Hukum, 2025)
The aim of this research is to analyze and discover the criminal liability arrangements for perpetrators of trafficking in protected animals in Indonesia, and to find out and analyze the criminal liability of perpetrators of trafficking in protected animals from the perspective of laws and regulations in Indonesia. The problems of this research are 1) How is the criminal responsibility regulated for perpetrators of trafficking in protected animals in Indonesia? 2) What is the criminal liability of perpetrators of trafficking in protected animals from Indonesian laws and regulations perspective of? This research is a normative juridical research with a statutory approach, conceptual approach and case approach. The results of the research show that firstly, the regulation of criminal liability for perpetrators of trafficking in protected animals in Indonesia is specifically regulated in legislation in the field of conservation of biological resources and ecosystems, which emphasizes criminal liability for perpetrators with imprisonment and fines. Secondly, criminal liability for perpetrators of trafficking in protected animals from the perspective of laws and regulations in Indonesia, must be carried out by making efforts to amend the Law on Conservation of Living Natural Resources and their Ecosystems, in order to create regulatory efforts that meet the characteristics of criminal liability, namely the existence of balance. between law and morals, holistic justice enforcement, flexibility in legal interpretation, community participation, and prevention aspects.